Knowledge-Aided Normalized Iterative Hard Thresholding Algorithms for Sparse Recovery - Jiang, Qianru; de Lamare, Rodrigo C.; Zakharov, Yuriy; Li, Sheng; He, Xiongxiong (2018 26th European Signal Processing Conference (EUSIPCO), 2018)
This paper deals with the problem of sparse recovery often found in compressive sensing applications exploiting a priori knowledge. In particular, we present a knowledge-aided normalized iterative hard thresholding (KA-NIHT) algorithm that exploits information about the probabilities of nonzero entries. We also develop a strategy to update the probabilities using a recursive KA-NIHT (RKA-NIHT) algorithm, which results in improved recovery. Simulation results illustrate and compare the performance of the proposed and existing algorithms.